ICT Innovations 2011 - Kocarev, Ljupco (Advances in Intelligent and Soft Computing, 2012)
Information and Communication Technologies has enlarged its horizon and it is practiced under multidisciplinary contexts that introduce new challenges to theoretical and technical approaches. The most critical benefit of introducing new ICT technologies in our real world living are the new ways of working that the online world makes possible. Complexity, uncertainty and scaling issues of real world problems as well as natural phenomena in ecology, medicine and biology demanding ICT assistance create challenging application domains for artificial intelligence, decision support and intelligence systems, wireless sensor networks, pervasive and ubiquitous computing, multimedia information systems, data management systems, internet and web applications and services, computer networks, security and cryptography, distributed systems, GRID and cloud computing. This book offers a collection of papers presented at the Third International Conference on ICT Innovations held in September 2011, in Skopje, Macedonia. The conference gathered academics, professionals and practitioners in developing solutions and systems in the industrial and business arena especially innovative commercial implementations, novel applications of technology, and experience in applying recent ICT research advances to practical solutions.